Expression profiling and in situ screening of circular RNAs in human tissues. Issue 1 (December 2018) - Zaghlool, Ammar; Ameur, Adam; Wu, Chenglin; Westholm, Jakub; Niazi, Adnan; Manivannan, Manimozhi; Bramlett, Kelli; Nilsson, Mats; Feuk, Lars
Abstract Circular RNAs (circRNAs) were recently discovered as a class of widely expressed noncoding RNA and have been implicated in regulation of gene expression. However, the function of the majority of circRNAs remains unknown. Studies of circRNAs have been hampered by a lack of essential approaches for detection, quantification and visualization. We therefore developed a target-enrichment sequencing method suitable for screening of circRNAs and their linear counterparts in large number of samples. We also applied padlock probes andin situ sequencing to visualize and determine circRNA localization in human brain tissue at subcellular levels. We measured circRNA abundance across different human samples and tissues. Our results highlight the potential of this RNA class to act as a specific diagnostic marker in blood and serum, by detection of circRNAs from genes exclusively expressed in the brain. The powerful and scalable tools we present will enable studies of circRNA function and facilitate screening of circRNA as diagnostic biomarkers.